Cardiovascular mortality rate in Moscow and St. Petersburg in 2015 and 2018 - S. A. Boytsov; E. Z. Golukhova; O. M. Drapkina; O. V. Zayratyants; I. V. Samorodskaya; V. Yu. Semenov (Российский кардиологический журнал)
The differences in mortality rates between Moscow and St. Petersburg require study.Aim. Ranking and comparison of cardiovascular mortality in Moscow and St. Petersburg in 2015 and 2018.Material and methods. Data on the population and mortality rates was assessed according to the Brief nomenclature of causes of death of Federal State Statistic Service. Eleven out of 35 nomenclature lines related to cardiovascular disease (CVD) are represented by 4-digit ICD codes, the rest are represented by groups with 3- and/or 4-digit codes. Standardized mortality rates (SMRs) were calculated based on the European standard. Comparison of SMR differences between Moscow and St. Petersburg in 2015 and 2018 was carried out using the nonparametric Wilcoxon test.Results. The proportion of CVD in all-cause SMR in both cities is about 50%. There were no significant differences in SMR (2018-2015) between Moscow and St. Petersburg for 35 CVDs. The first 3 ranking places in the CVD pattern both in Moscow and St. Petersburg were occupied by CAD, different types of chronic CAD, and stroke. In 2015, their proportion was 58,3% and 48,9% and in 2018, 52,7% and 58,7%. Other causes varied significantly in relation to SMR and ranks in different years, which is probably due to different approaches to determining the code of death cause. The SMR and myocardial infarction contribution to cardiovascular mortality decreased.Conclusion. Differences in cardiovascular mortality between Moscow and St. Petersburg remain. To understand the mortality causes and to develop effective programs to reduce it, it is necessary to eliminate the identified defects.